The retrospective approach in historical geography - Gulley, J. L. M. (ERDKUNDE, 1961)
Historical-geographical research is often concerned with establishing the age of elements of the present cultural landscape. Such research progresses from the present to the past, from the more source-rich to the less source-poor period, and there is general agreement that this type of research is generally valuable and sometimes the only one possible. Rarely, however, are the results of such research also presented in the same retrogressive manner, and in those cases where such a framework for presentation has been chosen, as by P. Deffontaines, this method has been criticized- The criticism is expressed. as being that the retrogressive presentation is fraught with fundamental theoretical weaknesses. Further reflection, however, suggests that the criticism has been challenged by inconsistent procedures in these studies, and that if the method is applied consistently, the backward-stepping presentation of research results has fundamental advantages. Its greatest strength is that it reflects the actual progress of the research; new facts and results can be easily pointed out, while gaps in knowledge are also clearly highlighted. This contrasts with the presentation of change in the form of a chronologically progressive narrative, which often passes over sections about which there is insufficient knowledge in silence so as not to disrupt the flow of the narrative. Of course, the retrograde narrative also has its own weaknesses and difficulties, but in view of its strengths, which it undoubtedly possesses, it should not be completely forgotten.